Treatment of Chemically Synthesized Polyaniline Wastewater by Combining Adsorption of Activated Carbon and Neutralization of Calcium Carbonate - Ju, Qingqing; Huang, Han; Kan, Jinqing (Asian Journal of Chemistry, 2013)
The purpose of this work was to study the treatment of polyaniline wastewater by adsorption of activated carbon and neutralization of calcium carbonate. The polyaniline wastewater generated in the synthesis process contained toxic aniline and its derivatives, which would pollute water and pose severe harm for human health and environment. Activated carbon is a strong adsorbent that could adsorb aniline and its derivatives effectively. Batch experiments such as the concentration of the polyaniline wastewater, adsorbent dose, contact time and pH were carried out to investigate the optimal treatment conditions. Results showed that the optimum conditions were at dilution concentration of 0.08 times of the raw concentration, 16.0 g L-1 activated carbon, 0.5 h and the original pH 1.05. About 91 % organics removal percentage could be reached by this method. Chemical oxygen demand (COD) of the polyaniline wastewater before and after treatment is 838 and 75 mg L-1, respectively and the removal efficiency was more than 91 %. The polyaniline wastewater after adsorption treatment was neutralized to pH 6.7 by 8 g L-1 CaCO3.